If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 8 = 1x + 92 Reorder the terms: 8 + 13x = 1x + 92 Reorder the terms: 8 + 13x = 92 + 1x Solving 8 + 13x = 92 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 8 + 13x + -1x = 92 + 1x + -1x Combine like terms: 13x + -1x = 12x 8 + 12x = 92 + 1x + -1x Combine like terms: 1x + -1x = 0 8 + 12x = 92 + 0 8 + 12x = 92 Add '-8' to each side of the equation. 8 + -8 + 12x = 92 + -8 Combine like terms: 8 + -8 = 0 0 + 12x = 92 + -8 12x = 92 + -8 Combine like terms: 92 + -8 = 84 12x = 84 Divide each side by '12'. x = 7 Simplifying x = 7
| (2b+7)(3b-c+9)= | | 4-6.25x=3.8x | | 20x-4.9x^2=0 | | 2k=-24 | | 2(5y-6)=-2 | | 5-2x+3=-8+2x | | -6y+4=76 | | 20=0.18t^3-2.16t^2+4.86t | | 9x^2+4x-44=0 | | (a-3)(6a+7)= | | 4.3=0.5 | | 5=2t | | 1-5xy^2c-3x^2+c=5xyc-4x+3x^2c | | 16-2x=-8x+10 | | (3x-1)(2x+2)= | | 12x-16=2x+14 | | 10x+3(2x+5)=5 | | 46+4x=6x+76 | | 28-3(4-x)=-2 | | 28-3(4-x)=-2 | | 28-3(4-x)=-2 | | 3x+25=40-17x | | -22-y=10 | | m^3+m^2+1=0 | | -7.5n+1.4=-6.1 | | 26+12f=50 | | 9y+7=0 | | (p^3-3p^2+5p)-(-4p^3-3p^2-8p)= | | g(2g+4)(g+2)=0 | | t+y=n | | 2x+3.9=7.7 | | p-21-21=3 |